CaMKII versus DAPK1 Binding to GluN2B in Ischemic Neuronal Cell Death after Resuscitation from Cardiac Arrest - Buonarati, Olivia R. (Cell Rep, 2020)
DAPK1 binding to GluN2B was prominently reported to mediate ischemic cell death in vivo. DAPK1 and CaMKII bind to the same GluN2B region, and their binding is mutually exclusive. Here, we show that mutating the binding region on GluN2B (L1298A/ R1300Q) protected against neuronal cell death induced by cardiac arrest followed by resuscitation. Importantly, the GluN2B mutation selectively abolished only CaMKII, but not DAPK1, binding. During ischemic or excitotoxic insults, CaMKII further accumulated at excitatory synapses, and this accumulation was mediated by GluN2B binding. Interestingly, extra-synaptic GluN2B decreased after ischemia, but its relative association with DAPK1 increased. Thus, ischemic neuronal death requires CaMKII binding to synaptic GluN2B, whereas any potential role for DAPK1 binding is restricted to a different, likely extra-synaptic population of GluN2B.